Cold War on CNN, Part 14: Red Spring: The Sixties (United Kingdom : Jeremy Isaacs Productions, 1998)
In the 1960s, as dissent and protest swept through the West, nations of the Warsaw Pact were experimenting with reforms. But hopes for change were crushed by palace coups and, in the case of Czechoslovakia, outright invasion.
Keywords: United Kingdom